Dynamically Reconfigurable Short‐Term Synapse with Millivolt Stimulus Resolution Based on Organic Electrochemical Transistors. Issue 9 (4th August 2019) - Ling, Haifeng; Wang, Naixiang; Yang, Anneng; Liu, Yanghui; Song, Jiajun; Yan, Feng
Abstract: Electrolyte‐gated organic electrochemical transistors (OECTs) are attractive for synaptic electronics owing to the ionic–electronic coupling, huge specific capacitance, physiological environmental compatibility, and architectural flexibility. Here, an identical spike‐polarity method is reported to realize the concomitance of excitatory and inhibitory short‐term plasticities in unipolar poly(3, 4‐ethylenedioxythiophene)–poly(styrenesulphonate) (PEDOT:PSS) OECTs. Dynamical reconfiguration between the excitatory and inhibitory responses with multilevel and well‐balanced synaptic strength is realized, without performing operations or introducing additional modulation terminals. Owing to the distinctive volumetric capacitance of OECTs, the PEDOT:PSS synapse affords remarkable characteristics such as an ultrahigh stimulus‐resolution capability of 10 mV and an ultralow power consumption of ≈2 pJ per spike. Moreover, spatiotemporal‐correlated logics is realized. This work demonstrates on‐demand manipulation of ionic dynamics for building synaptic elements with sophisticated functionalities at a single‐device level. Abstract : Dynamically reconfigurable short‐term synapses are demonstrated based on poly(3, 4‐ethylenedioxythiophene)–poly(styrenesulphonate) (PEDOT:PSS) organic electrochemical transistors. The concomitant and independently expressed excitatory and inhibitory plasticities are emulated in a single transistor without additional modulation terminals. Remarkable performances including 10 mV ultrahigh stimulus‐resolution and 2 pJ per spike ultralow power consumption are obtained.